Multiplicity of crime and its impact on the criminal rules of jurisdiction - Mohammed Hussein Mohammed Al-Hamadani (الرافدین للحقوق, 2012)
Many juriss and expositors of international law call… todeminish the ex-meaning of sovereignty in fields of p the enable international law bay substituting it for the nation of competence. Despite this , the public international law did not get rid of the results of sovereignty notion in its traditional meaning completely. But in the wake of world two wars in nineteenth century ,the majority of these jurists and expositors call to modulate the absolute state sovereignty and subject it to public international rules. It is mentioned in the declaration of rights and obligations of states that sovereignty of states must subject to the sovereignty of international law besides many decisions of international court of justice have showed that rights resulted from sovereignty of state should be exercised in away which does not oppose with the obligations of state under the international convention .so long as this convention is achieved by fre will consequently ,the doctrine of asolute sovereignty according to the dominant jurisprudence of public international law and jurisdiction of international courts, the doctrine of absolute sovereignty is not regarded one of the doctrines. .